Gestaltphonologische Interpretation von Vokalsequenzierungen: eine Studie zum Portugiesischen, Spanischen, Französischen, Italienischen und Rumänischen - Teixeira Kalkhoff, Alexander M. (Beihefte zur Zeitschrift für romanische Philologie, 2021)
"This study presents a phenomenological approach to word-internal vowel sequencing. Diphthongs and hiatuses are thus not objects of examination a priori; instead, as relational sequencing patterns, they are effects of the Gestalt qualities that determine the word structure, which manifest in prominences, syllabification, rhythm, and temporal and phonetic structure, and keep the word recognizable as a whole in the flow of speech."--Publisher's website
Bibliographie: Seite [173]-198
Keywords: Hochschulschrift; Hiatus; Diphthong; Vokal; Rumänisch; Italienisch; Französisch; Spanisch; Portugiesisch; Romanische Sprachen